2020
DOI: 10.1111/pbi.13422
|View full text |Cite
|
Sign up to set email alerts
|

Superior haplotypes for haplotype‐based breeding for drought tolerance in pigeonpea (Cajanus cajan L.)

Abstract: Haplotype-based breeding, a recent promising breeding approach to develop tailor-made crop varieties, deals with identification of superior haplotypes and their deployment in breeding programmes. In this context, whole genome re-sequencing data of 292 genotypes from pigeonpea reference set were mined to identify the superior haplotypes for 10 droughtresponsive candidate genes. A total of 83, 132 and 60 haplotypes were identified in breeding lines, landraces and wild species, respectively. Candidate gene-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…We believe that one or a combination of the following three genomic breeding approaches, namely MAS/MABC, haplotype-based breeding (HBB) and genomic prediction, can be used to develop superior lines. While MAS/MABC has been successfully used for product development, HBB has shown huge potential for trait improvement in rice ( Abbai et al, 2019 ) and pigeonpea ( Sinha et al, 2020 ). During recent years the accuracy and prediction of predicting phenotypes in genomics selection has been improved extensively through approaches including (i) estimating global GEBVs while considering interaction of marker and environment covariates (G × E) ( Jarquín et al, 2014 ; Crossa et al, 2017 ), (ii) estimating haplotype/bin- based local GEBVs ( Voss-Fels et al, 2019 ), (iii) WhoGEM approach that explores the relationships between phenotypes and admixture components, land types, admixture components × environment interactions, and controls for the environment ( Gentzbittel et al, 2019 ), and (iv) optimal contribution selection method that enables simultaneous trait improvement and enriching the genetic base ( Woolliams et al, 2015 ; Cowling et al, 2017 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…We believe that one or a combination of the following three genomic breeding approaches, namely MAS/MABC, haplotype-based breeding (HBB) and genomic prediction, can be used to develop superior lines. While MAS/MABC has been successfully used for product development, HBB has shown huge potential for trait improvement in rice ( Abbai et al, 2019 ) and pigeonpea ( Sinha et al, 2020 ). During recent years the accuracy and prediction of predicting phenotypes in genomics selection has been improved extensively through approaches including (i) estimating global GEBVs while considering interaction of marker and environment covariates (G × E) ( Jarquín et al, 2014 ; Crossa et al, 2017 ), (ii) estimating haplotype/bin- based local GEBVs ( Voss-Fels et al, 2019 ), (iii) WhoGEM approach that explores the relationships between phenotypes and admixture components, land types, admixture components × environment interactions, and controls for the environment ( Gentzbittel et al, 2019 ), and (iv) optimal contribution selection method that enables simultaneous trait improvement and enriching the genetic base ( Woolliams et al, 2015 ; Cowling et al, 2017 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Retrospectively, targeted analysis of superior haplotypes across mega-varieties may help revealing combinations of superior haplotypes that explain the genetic basis of the highperformance of these lines. In pigeonpea, Sinha et al (2020) found complete absence of superior haplotypes for drought tolerance in popular varieties Maruti (ICP 8863) and Jagriti (ICPL 151), thus offering possibilities for further improvement of such high-yielding varieties. In parallel, increasing sequencing data on wild relatives will aid in the discovery of new haplotypes that the cultivated pool currently lacks.…”
Section: Haplotype-based Breedingmentioning
confidence: 99%
“…As has been demonstrated in rice, a panel of sequenced lines capturing the maximum diversity is deemed suitable for phenotypic validation of haplotypes defining key traits (Abbai et al ., 2019). A similar haplo‐pheno analysis in pigeonpea validated superior haplotypes of three genes for drought tolerance that were identified by mining of the WGRS data set and candidate gene‐based association analysis (Sinha et al ., 2020). The study also identified a set of promising lines carrying these superior haplotypes.…”
Section: Breeding Strategies To Deliver Higher Genetic Gainsmentioning
confidence: 99%
See 2 more Smart Citations